If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(3) + 1 = 10 Reorder the terms for easier multiplication: 3 * 3x + 1 = 10 Multiply 3 * 3 9x + 1 = 10 Reorder the terms: 1 + 9x = 10 Solving 1 + 9x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 9x = 10 + -1 Combine like terms: 1 + -1 = 0 0 + 9x = 10 + -1 9x = 10 + -1 Combine like terms: 10 + -1 = 9 9x = 9 Divide each side by '9'. x = 1 Simplifying x = 1
| 2x^2=51.85 | | m/17=9 | | 3y=3-x | | (3x+10)(3x+10)= | | x/-5-1=1 | | (12x^2(x^-3)^-4)/6x^5 | | 15x*4+18x=156 | | 2x+46+14-4x=16x+2x | | 8#/9=16 | | 8x-57=2x+3 | | dy/dx=cot^2x | | 4(5c+3)=9c+7 | | 30+(5y-8)+(11x-9)=180 | | 5x-3+4x*9-5x*3-4+2x-5+2=8 | | -11u-8+3u=247 | | dy/dx=cot^2 | | 18x=156 | | C/6-8=2 | | 2(4x-2)-5x=18 | | y=cot^2dx | | 4x*2*2-4x+3-5=5+0 | | 60x^2-59x-20=0 | | 4s+f=156 | | 5m-10=8m+14 | | -9v=-108 | | 5+4y+3y+2=1-2 | | (24m^-2n^4)^-2/(16m^3n^-5)^-2 | | 5+8+2+4x-8x+2+7+3=x | | 3x-4=1/4(12-16x) | | 5x-2+4+3x*6=28x-2-2 | | 41n(x-2)=-4 | | 4(x-5)=5(x+6) |